2023
DOI: 10.3390/machines11020158
|View full text |Cite
|
Sign up to set email alerts
|

A SLAM-Based Localization and Navigation System for Social Robots: The Pepper Robot Case

Abstract: Robot navigation in indoor environments has become an essential task for several applications, including situations in which a mobile robot needs to travel independently to a certain location safely and using the shortest path possible. However, indoor robot navigation faces challenges, such as obstacles and a dynamic environment. This paper addresses the problem of social robot navigation in dynamic indoor environments, through developing an efficient SLAM-based localization and navigation system for service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In this case, the three attempts failed regarding the expected route and the location of the final position. This is supported by Alhmiedat et al [20], who reported an average localization error of 0.51 m and 86% user acceptability.…”
Section: Map and Navigation Functionality Of Peppersupporting
confidence: 63%
See 1 more Smart Citation
“…In this case, the three attempts failed regarding the expected route and the location of the final position. This is supported by Alhmiedat et al [20], who reported an average localization error of 0.51 m and 86% user acceptability.…”
Section: Map and Navigation Functionality Of Peppersupporting
confidence: 63%
“…It facilitates the mapping of the environment and the location of objects to produce a safety map [14]. Alhmiedat et al [20] highlighted the problems with Pepper's navigation system. Gomez et al [21] mentioned that due to the small-range LIDARs and RGB, Pepper is not able to self-localize in larger surroundings.…”
Section: Related Workmentioning
confidence: 99%
“…The process by which a robot selects its own position, direction, and path to reach a destination is referred to as robot navigation. Mobile robots utilize a variety of sensors to scan the environment and gather geometric information about the area of interest [5]. The authors of [6] revealed that the creation or representation of a map is achieved through the simultaneous localization and mapping (SLAM) approach.…”
Section: Introductionmentioning
confidence: 99%
“…synchronous positioning and mapping (SLAM) technology is also a commonly technology in advanced sweeping robots. SLAM combines data from multiple sensors, such as cameras and laser rangefinders, and allows robots to navigate autonomously by continuously updating maps and positions [3]. Sweeping robots use various positioning technologies to navigate effectively and clean different types of spaces, and adapt to the layout and obstacles in the environment.…”
Section: Introductionmentioning
confidence: 99%